Mesopithecus pentelicus from the Turolian locality of Kryopigi (Kassandra, Chalkidiki, Greece). Issue 121 (August 2018) - Lazaridis, Georgios; Tsoukala, Evangelia; Rae, Todd C.; Gómez-Olivencia, Asier; Nagel, Doris; Bartsiokas, Antonis
Abstract: New material of the Mio-Pliocene colobine Mesopithecus from the Turolian locality of Kryopigi (Greece) is described here. It includes a complete skull with the atlas attached and other dental and postcranial elements representing at least five individuals (four males and one female). The material is compared with Mesopithecus delsoni, Mesopithecus pentelicus, Mesopithecus monspessulanus and intermediate forms from more than a dozen Turolian localities of the Greco-Iranian province. These comparisons support the attribution of the Kryopigi material to M. pentelicus . The chronostratigraphic distribution of Mesopithecus species and intermediate forms suggests that the Kryopigi fauna could be dated as younger than the Perivolaki locality with M. delsoni/pentelicus (7.1–7.3 Ma, MN12) and older than the Dytiko localities with M. aff. pentelicus, M. cf. pentelicus and M. cf. monspessulanus (?middle MN13). The dimensions of the atlas are within the distribution of extant colobines. The skull shows bite-marks, probably caused by the hyaena Adcrocuta eximia .